2017
DOI: 10.3390/en10030341
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Silicon Carbide Power Packaging—Past Trends, Present Practices, and Future Directions

Abstract: This paper presents a vision for the future of 3D packaging and integration of silicon carbide (SiC) power modules. Several major achievements and novel architectures in SiC modules from the past and present have been highlighted. Having considered these advancements, the major technology barriers preventing SiC power devices from performing to their fullest ability were identified. 3D wire bondless approaches adopted for enhancing the performance of silicon power modules were surveyed, and their merits were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…Silicon carbide (SiC) is a refractory compound semiconductor material that has many unique and desirable electrical, mechanical, and chemical properties including high melting point, low density, good mechanical behavior, resistance to oxidation at high temperature and chemical inertness to corrosive media. In addition to its application in high power electronic devices with the ability to operate at temperatures as high as 600°C, [1][2][3] SiC has several other high temperature applications including nuclear materials, [4][5][6] reinforced composites, 7 and the hot cell of thermionic energy converters. 8,9 Tungsten (W) is one of the preferred ohmic contact metals on SiC for semiconductor device applications due to its high melting point (3400°C), high temperature stability, inherent heat resistance, and high thermal conductivity, as well as excellent corrosion and abrasion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon carbide (SiC) is a refractory compound semiconductor material that has many unique and desirable electrical, mechanical, and chemical properties including high melting point, low density, good mechanical behavior, resistance to oxidation at high temperature and chemical inertness to corrosive media. In addition to its application in high power electronic devices with the ability to operate at temperatures as high as 600°C, [1][2][3] SiC has several other high temperature applications including nuclear materials, [4][5][6] reinforced composites, 7 and the hot cell of thermionic energy converters. 8,9 Tungsten (W) is one of the preferred ohmic contact metals on SiC for semiconductor device applications due to its high melting point (3400°C), high temperature stability, inherent heat resistance, and high thermal conductivity, as well as excellent corrosion and abrasion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The next driver for progress is considered to be integration and packaging [1], [5]- [8]. Future packaging technologies should offer better electrical and thermal performances, low cost, and should be able to manage the complexity of the multi-cellular approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The higher operating temperature afforded by next-generation power semiconductors can reduce the cooling requirements, thereby reducing the overall size and weight of a system. Likewise, higher switching frequencies offered by these devices directly correlates to a reduction in both the size and weight of system-level passive components [12], [22]. Furthermore, integration of some of these passive components inside the module can have a profound impact on power density.…”
Section: Power Module Designmentioning
confidence: 99%
“…Research in this area by incorporating 3D packaging techniques has shown reduction in EMI as well as the benefits associated with a 3D structure. These include higher power density and the possibility for double-sided cooling [22], [26], [27]. Fig.…”
Section: Power Module Designmentioning
confidence: 99%
See 1 more Smart Citation